Antimicrobial sales profile in Brazil from 2014 to 2021: analysis of records from the National System of Controlled Products Management - Jakeline Ribeiro Barbosa; Giovanny Vinícius Araújo de França; Aurélio Matos Andrade; Beatriz Torres Araújo; Cláudio Maierovitch Pessanha Henriques; Mariana Pastorello Verotti (Revista Brasileira de Epidemiologia)
ABSTRACT Objective: To analyze the antimicrobial dispensing profile in Brazil from 2014 to 2021 based on records from the Brazilian National System of Controlled Products Management (SNGPC) of the Brazilian Health Regulatory Agency (Anvisa). Methods: A descriptive, time-series ecological study was carried out using data from private pharmacies and drugstores on the sale of antimicrobial drugs. Drugs sold from January 2014 to November 2021 were included, with analysis of the variables of month, year, municipality, state, active ingredient, prescriber’s professional council, and patient’s sex and age. Results: During the study period, 532,518,866 sales of special control drugs were recorded in SNGPC, 66.8% of which were antimicrobials. There was an increase in sales up to 2019, with a decrease in 2020, during the COVID-19 pandemic, and a new increase in 2021. The Southeast and Northeast regions concentrated the highest sales, with the Southeast leading. Sales were higher among women, especially in the 30 to 44.9 age group, with an increase in sales among patients aged 60 or older. The best-selling antimicrobials were amoxicillin, azithromycin, ciprofloxacin and cephalexin. Conclusion: The study reveals differences in consumption by region, sex, and age, and it highlights the importance of educational interventions for the responsible use of antimicrobials. It also points out that the suspension of mandatory data registration in SNGPC may compromise the monitoring necessary to combat bacterial resistance and improve public health in Brazil.